Kinematics and dynamics analysis of a novel five-degrees-of-freedom hybrid robot. (23rd June 2017) - Wu, You; Yang, Zhen; Fu, Zhuang; Fei, Jian; Zheng, Hui
In this article, a novel five-degrees-of-freedom hybrid robot is proposed and its kinematics and dynamics are analyzed systematically. First, the mechanism is designed. It is composed of a traditional three-degrees-of-freedom delta robot and a two-degrees-of-freedom serial mechanism. Second, the forward kinematics is established by geometric method, and the inverse kinematics is established by Denavit-Hartenberg (D-H) matrix method. Third, based on the principle of virtual work, Lagrange equations of dynamics are deduced. Finally, the feasibility and advantage of the proposed robot are verified by simulation and experiment.